Apoptosis and age-dependant induction of nuclear and mitochondrial etheno-DNA adducts in Long-Evans Cinnamon (LEC) rats: enhanced DNA damage by dietary curcumin upon copper accumulation - Nair, Jagadeesan; Frank, Norbert; Bartsch, Helmut (Carcinogenesis, 2005)
Long-Evans Cinnamon (LEC) rats, a model for human Wilson's disease, develop chronic hepatitis and liver tumors owing to accumulation of copper and induced oxidative stress. Lipid peroxidation (LPO)-induced etheno-DNA adducts in nuclear- and mitochondrial-DNA along with apoptosis was measured in LEC rat liver. Levels of etheno-DNA adducts (1, N6 -ethenodeoxyadenosine and 3, N4 -ethenodeoxycytidine) increased with age reaching a peak at 8 and 12 weeks in nuclear and mitochondrial DNA, respectively. This is the first demonstration that etheno-DNA adducts are also formed in mitochondrial DNA. Apoptosis was assessed by TUNEL + cells in liver sections. CD95L RNA expression was also measured by in situ hybridization in the same sections. The highest nuclear DNA adduct levels coincided with a reduced apoptotic rate at 8 weeks. Mitochondrial-DNA adducts peaked at 12 weeks that coincided with the highest apoptotic rate, suggesting a link of etheno-DNA adducts in mitochondrial DNA to apoptosis. The DNA damage in liver was further enhanced and sustained by 0.5% curcumin in the diet. Treatment for 2 weeks elevated etheno-DNA adducts 9- to 25-fold in nuclear DNA and 3- to 4-fold in mitochondrial-DNA, providing a plausible explanation as to why in our earlier study [Frank et al . (2003) Mutat. Res. , 523-524, 127-135], curcumin failed to prevent liver tumors in LEC rats. Our results also confirm the reported in vitro DNA damaging potential of curcumin in the presence of copper ions by reactive oxygen species. LPO-induced adduct formation in nuclear and mitochondrial DNA appear as early lesions in LEC rat liver carcinogenesis and are discussed in relation to apoptotic events in the progression of malignant disease.